Current and Emerging Options for the Management of Inherited von Willebrand Disease - Heijdra, Jessica M. (Drugs, 2017)
Von Willebrand disease (VWD) is the most common inherited bleeding disorder with an estimated prevalence of ~1% and clinically relevant bleeding symptoms in approximately 1:10,000 individuals. VWD is caused by a deficiency and/or defect of von Willebrand factor (VWF). The most common symptoms are mucocutaneous bleeding, hematomas, and bleeding after trauma or surgery. For decades, treatment to prevent or treat bleeding has consisted of desmopressin in milder cases and of replacement therapy with plasma-derived concentrates containing VWF and Factor VIII (FVIII) in more severe cases. Both are usually combined with supportive therapy, e.g. antifibrinolytic agents, and maximal hemostatic measures. Several developments such as the first recombinant VWF concentrate, which has been recently licensed for VWD, will make a more “personalized” approach to VWD management possible. As research on new treatment strategies for established therapies, such as population pharmacokinetic-guided dosing of clotting factor concentrates, and novel treatment modalities such as aptamers and gene therapy are ongoing, it is likely that the horizon to tailor therapy to the individual patients’ needs will be extended, thus, further improving the already high standard of care in VWD in most high-resource countries.